2019
DOI: 10.3389/fphys.2019.01207
|View full text |Cite|
|
Sign up to set email alerts
|

TRPV1 and TRPV1-Expressing Nociceptors Mediate Orofacial Pain Behaviors in a Mouse Model of Orthodontic Tooth Movement

Abstract: Orthodontic force produces mechanical irritation and inflammation in the periodontium, which is inevitably accompanied by pain. Despite its prevalence, treatment of orthodontic pain is ineffective. Elucidating underlying neural mechanisms is critical to improving the management of orthodontic pain. We have assessed the contribution of transient receptor potential vanilloid subtype 1 (TRPV1) and the TRPV1-expressing subset of nociceptive afferents to pain behaviors induced by orthodontic force in mice. Microfoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 38 publications
1
39
1
Order By: Relevance
“…In rats, limited studies were carried out into sex differences but no differences were found in the original validation study [ 21 ], or in a later study [ 70 ]. Unfortunately, it appears that most grimace studies in rats and mice appear to have been conducted in one sex, with a large proportion using male animals, see e.g., [ 52 , 71 , 72 , 73 ]. This bias in study design toward males, coupled with the enhanced understanding of the existence of different pathways and immune-cell types for pain processing between male and female rodents [ 74 ], renders extrapolation of findings to female rodents problematic.…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
“…In rats, limited studies were carried out into sex differences but no differences were found in the original validation study [ 21 ], or in a later study [ 70 ]. Unfortunately, it appears that most grimace studies in rats and mice appear to have been conducted in one sex, with a large proportion using male animals, see e.g., [ 52 , 71 , 72 , 73 ]. This bias in study design toward males, coupled with the enhanced understanding of the existence of different pathways and immune-cell types for pain processing between male and female rodents [ 74 ], renders extrapolation of findings to female rodents problematic.…”
Section: Clinical Applicability Of Grimace Scales In Biomedical Rementioning
confidence: 99%
“…Our group also found that AMPK‐α1 knockout (AMPK‐α1 ‐/‐ ) mice presented larger inflammatory periodontal bone defects and expressed higher levels of inflammatory cytokines than wild‐type (WT) mice 23 . Interestingly, OTM is a biomechanical process accompanied by tension side bone regeneration and pressure side bone resorption, which indicates the AMPK activation in the inflammation‐mediated osteogenesis under biomechanical irritation 24 …”
Section: Introductionmentioning
confidence: 67%
“…23 Interestingly, OTM is a biomechanical process accompanied by tension side bone regeneration and pressure side bone resorption, which indicates the AMPK activation in the inflammation-mediated osteogenesis under biomechanical irritation. 24 Current in vitro observations grounded on the static-culturing periodontal ligament cells (PDLCs), which led to big inconsistency from the actual stress state of the PDLCs during OTM. In this study, we focused on the anti-inflammation effect of SMV on tensile side of the orthodontic moving tooth in a rodent model.…”
mentioning
confidence: 99%
“…Unfortunately, it appears that most grimace studies in rats and mice appear to have been conducted in one sex, with a large proportion using male animals see eg. 52,[71][72][73] . This bias in study design towards males, coupled with the enhanced understanding of the existence of different pathways and immune-cell types for pain processing between male and female rodents 74 , renders extrapolation of findings to female rodents problematic.…”
Section: Strain and Sex Differencesmentioning
confidence: 99%